OPTIMIZED HYBRID IMAGE SECURITY SCHEME FOR COPYRIGHT PROTECTION, AUTHENTICATION AND CONFIDENTIALITY USING PSO - K. Kuppusamy; K. Thamodaran (European Scientific Journal, ESJ, 2013)
The digital watermarking scheme provides copyright protection, the hash function provides an authentication, and an encryption scheme provides security against illegal duplication and manipulation of multimedia contents especially to digital images. In this paper an optimized hybrid image security scheme for copyright protection, authentication and security of digital images using Particle Swarm Optimization(PSO) in daubechies4 wavelet transform is proposed. This scheme provide solutions to the issues such as copyright protection, authentication, robustness, security, statistical attacks and confidentiality. The coefficients are selected in daubechies4 domain with help of PSO to embed the DCT transformed selected high energy coefficients watermark bits in the host image. The features are extracted in daubechies4 domain with help of particle swarm optimization(PSO) to generate the image hash. The selected coefficients are encrypted in Daubechies4 domain with help of PSO. The image quality index metrics (IQIM) is used to measure the image quality distortion. The experimental results are evaluated with respect to BCR, CoS, IQIM, PSNR,and correlation and presented to demonstrate the competence of the proposed scheme.